The boy in the striped pajamas : a fable - Boyne, John, 1971- (Oxford ; New York : David Fickling Books, 2006)
Bored and lonely after his family moves from Berlin to a place called "Out-With" in 1942, Bruno, the son of a Nazi officer, befriends a boy in striped pajamas who lives behind a wire fence.
Accelerated Reader/Renaissance Learning
Man Booker Prize, 2006, considered
Keywords: Auschwitz (Concentration camp) -- Juvenile fiction; Auschwitz (Concentration camp) -- Fiction; Concentration camps -- Poland -- Fiction; Friendship -- Fiction; Nazis -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; World War, 1939-1945 -- Jews -- Fiction; Auschwitz -- Konzentrationslager; Deutscher Junge; Freundschaft; Gefangener; Junge; 2006.; Jugendbuch